ANALISIS KINERJA KEUANGAN DENGAN MENGGUNAKAN PENDEKATAN VALUE FOR MONEY PADA SATUAN KERJA IAIN SULTAN AMAI GORONTALO PERIODE TAHUN 2019-2021 - najma pettasolong; Yulia Gobel; Arafah Kurniawan (Department of Islamic Accounting, Faculty of Islamic Economics and Business, IAIN Sultan Amai Gorontalo, 2022)
This study aims to measure the financial performance of the IAIN Sutan Amai Gorontalo work unit, using the Value For Money approach by analyzing the 2019 to 2020 Budget Realization Report. The method used is descriptive qualitative using a comparative value based on value for money by calculating the economic value, effectiveness value and Efficiency value. The data was obtained through a document study in the form of secondary data reports on the realization of the 2019 to 2020 budget. each economic value < 100, Effectiveness value > 100 and Efficient value > 100, so it is said that the budget realization report of IAIN Sultan Amai Gorontalo for 2019, 2020 and 2021 meets the elements of being economical, efficient and effective.